Características de crecimiento de gramíneas tropicales en banco de germoplasma en la estación experimental “El Padmi” de la UNL. - Maldonado Jaramillo, José Luis (2024)
The growth and production of grasses depends on edaphoclimatic factors such as soil textura, fertility, and pH, as well as temperatura, precipitation and light. The objetive of this study was to evaluate the growth and production characteristicspf tropical forage grasses under the edaphoclimatic conditions of southern Ecuadorian Amazonia. To this end, a germplasm bank with 20 species was established at the experimental farm “El Padmi” of the National University of Loja. Data on plant height number of stems, number of leaves, coverage percentage, green forage production, dry matter content, and dry matter yield were collected and recorded at 30, 60, and 90 days of age. The data were analyzed using analysis of variance with a completely randomized design and Tukey’s test at a 0.05 significance level. The results showed statistical differences according to age for all variables. The grasses King Grass (P. purpureum x P. typoide), Elephant Grass (Pennisetum purpureum), Maralfalfa (Pennisetum sp.), and Cuba OM-22 (Pennisetum sp.) achieved the highest averages at 90 days of age, with values of 3.3 m for plant height; 40.5 stems per plant; 15.8 leaves per stem; 100% coverage; 102.7 t/ha/cuto f green forage; and 22.1 t/ha/cuto f dry matter. It is concluded that species of the genus Pennisetum adapt better to the edaphoclimatic conditions of the region, making them a Good alternative as forage Banks to supplement cattle feeding in the province of Zamora-Chinchipe.